Town Crying and the Gale of Sensitising Nigerian Rural Communities in the Face of a Pandemic: A Case of Corona Virus - Omoha, Alfred O.; Iorlaha, Lawrence Y.; Adoyi, Sylvester F. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
This study assesses town crying and the gale of sensitising Nigerian rural communities in the face of a pandemic with a special focus on the coronavirus pandemic. Among other things it seeks to ascertain if town criers informed the rural people about the coronavirus. A survey research design with a questionnaire as the instrument of data collection was adopted to elicit data from sixty town criers selected across Benue State through the use of purposive sampling. Findings reveal few town criers passed information to the rural people about COVID-19. It was also revealed that town criers in the state faced a lot of challenges and the most pronounced of them was the lack of megaphones to propel their voices. It was concluded that town criers were underused to disseminate information about COVID-19. It was therefore recommended that healthcare providers should always make use of town criers to pass health information to the rural people. This is considered necessary because the rural people understood the language of town criers and could ask for clarification where necessary.